Managing passengers' experience through mobile moments. (July 2017) - Inversini, Alessandro
Abstract: Travelers' experience is dramatically affected by the use of digital technologies. On the one side, travel companies use them to support management and marketing practices with the purpose of fostering efficiency and ultimately increase competitiveness. On the other side, travelers heavily rely on their digital devices to organize, personalize and to a certain extent 'live' their travelling experience. Within this scenario, mobile devices are seen from both ends as crucial mean for location and context based interactive communication. Mobile devices are here discussed as personalization tool for leisure air passengers' experiential journey in an airport starting from customers' journey analysis, along with information sources used within the whole journey. Highlights: Airport passengers' end-to-end experience is variegated and complex to study. Mobile phones are assuming a great role in supporting customer experience and interaction with organizations. Mobile touchpoints are great occasions for organizations to engage with customers and to deliver value added information. Based on 170 semi structured interview and on secondary research, this study shed lights on passengers' end-to-end journey. Within the passengers' journey the potentials of mobile devices as point of contact and engagement are highlighted.